The Okavango delta through the deformation of its surface : multi-proxy approach from hydrology to tectonics - (:unkn) unknown (My University, 2018)
The Okavango Delta is an endorheic system forming an alluvial fan in the Kalahari depression. The local ecosystem is paced by the annual flood coming from the Angolan highlands, blocked downstream by the normal faults scarps of the Okavango graben. This annual regime is highly variable, with the spatial distribution of the flood differing every year. At the geological time scale, from millenary to mega-annual, the Delta's endorheism can also vary between wetlands (current regime), mega-lake or loose its endorhism to turn into a river. Processes driving these regime variations are 1) the hydrological system, 2) the faulting of the graben, 3) the sedimentary input and 4) the ecosystem. This study brings quantitative constraints regarding two of these processes through the deformation of the Earth's ground surface monitored by permanent GPS stations. The observed signal is impacted seasonally by the hydrological loading resulting from the rainy season, and inter-annually by the variations of the terrestrial water storage, as well as the tectonic activity of the graben. GRACE satellites provide a quasi-continuous record of the variations of the Earth's continental water storage, allowing the modelling of the elastic deformation imposed on the Earth's crust by loading. The resulting modelled deformation signal is well correlated to the observed seasonal signal, hence validating the GRACE data products and revealing a large aquifer in the Okavango basin. GRACE thus provides a new proxy to monitor the evolution of water storage, and to validate more robustly the hydrological model calibrated for the basin. The variations in terrestrial water storage (TWS) in the basin validated by GRACE confirm the buffer effect of the aquifer in the modulation of climatic variations. The phase of the TWS variations moreover highlights a threshold in the recharge of TWS during the rainy season, depending on the intensity of the first rains. Finally, the poor spatial resolutio
Keywords: African Research